Analisis Penilaian dalam Konferensi Media antara Pemerintah Indonesia dan Australia Menuju Normalisasi Hubungan Bilateral - Rosaria Mita Amalia; Fauzia Zahira Munirul Hakim (Intermestic: Journal of International Studies, 2017)
This descriptive study aims to identify and analyze the types of appraisal found in the media conference between the Indonesian government and the Australian government in 2013. Appraisal is the evaluation of available types of attitudes delivered within a discourse. There are three types of attitudes in appraisal: affect, judgment, and appreciation. Affect is a means of how individuals express their feelings in discourse. Judgment is divided into personal judgment and moral judgment. Personal judgment includes individual’s admiration or criticism, while moral judgment includes individual’s praise or condemnation. Appreciation concerns individual’s attitudes towards surrounding things. The result shows that there is no negative appraisal proposed by the representatives of both governments. Both representatives agreed to continue and restore the almost damaged bilateral relations after the surveillance scandal conducted by the Australian government to President Susilo Bambang Yudhoyono.